IMPROVEMENT THE Ca-Mg MINERAL RATIO OF MEDIA CULTIVATION ON STRESS LEVELS IN FRESHWATER PRAWNS (MACROBRACHIUM ROSENBERGII) - Lalu Mukhtar Atmawinata; Sahrul Alim; Andre Rachmat Scabra (Universitas Mataram, 2024)
Freshwater prawns (Macrobrachium rosenbergii) are a freshwater species that is intensively cultivated. Calcium (Ca) and magnesium (Mg) are important factors in supporting the biological and physiological activities of freshwater prawns. The presence of minerals in the form of calcium and magnesium in the environment will be utilized by giant prawns, especially after the molting process. Calcium and magnesium important for the osmoregulation process and carapace formation of freshwater prawns. This research aims to see the best ratio of minerals in the form of calcium and magnesium to environmental stress in terms of the parameters of calcium and magnesium content in the prawns body, osmotic gradient, oxygen consumption level, and water quality during rearing. The experimental design used in this research was a completely randomized design (CRD) with five treatments and three replications. The treatment given consisted of increasing Ca-Mg in the media: A: 30 mg l-1 Ca + 0 mg l-1 Mg (1:0); B: 30 mg l-1 Ca + 15 mg l-1 Mg (1:0.5); C: 30 mg l-1 Ca + 30 mg l-1 Mg (1:1); D: 30 mg l-1 Ca + 45 mg l-1 Mg (1:1.5) and E: 30 mg l-1 Ca + 60 mg l-1 Mg (1:2). Based on the result, treatment C: 30 mg l-1 Ca + 30 mg l-1 Mg (1:1) can reduce osmotic gradient values, oxygen consumption levels and glucose levels.